Rationale and description of a lifestyle intervention programme to achieve moderate weight loss in women with non-metastatic breast cancer: the lifestyle intervention part of the SUCCESS C Study. Issue 2 (21st September 2020) - Hauner, Dagmar; Rack, Brigitte; Friedl, Thomas; Hepp, Philip; Janni, Wolfgang; Hauner, Hans
Abstract : Objective: There is growing evidence from observational studies that lifestyle factors such as obesity, an unhealthy diet and lack of physical activity are associated with poor long-term outcome in women with breast cancer. The primary objective of the lifestyle modification part of the Simultaneous Study of Docetaxel Based Anthracycline Free Adjuvant Treatment Evaluation, as well as Life Style Intervention Strategies (SUCCESS C) Trial is to investigate the effect of an individualised lifestyle intervention programme aiming at moderate weight loss on disease-free survival in women with HER2/neu-negative breast cancer. Secondary objectives include the effect of the intervention on body weight, cardiovascular risk and quality of life. Methods: The SUCCESS C Trial is an open-label, multicentre, randomised controlled phase III study using a 2×2 factorial design in women with newly diagnosed HER2/neu-negative intermediate-risk to high-risk breast cancer. The first randomisation served to compare disease-free survival in patients treated with two different chemotherapy regimens (3642 participants). The second randomisation served to compare disease-free survival in patients with a body mass index of 24–40 kg/m² (2292 participants) receiving either a telephone-based individualised lifestyle intervention programme for moderate weight loss or general recommendations for a healthy lifestyle for 2 years. Outcome analyses will be conducted after 5 years of follow-up. Perspective: This study will provide information on the efficacy and safety of a comprehensive lifestyle intervention programme on disease-free survival in a large cohort of women with breast cancer. EU Clinical Trials Identifier: 2008-005453-38.